The Cryptocurrency - Accounting Challenge - Brezoeva, Boika (Research Papers, 2020)
Cryptocurrency is а new accounting item, a product of modern technology and digitization of business life. Current accounting standards do not have clear accounting rules for the treatment of cryptocurrency and therefore a diversified accounting policies have been applied with prevailing measurement at fair value through profit or loss. However, this practice is limited by the Agenda Decision published by IFRS Interpretation Committee (IFRIC) in June 2019, which requires that cryptocurrency be accounted for as inventory when held for sale, and as an intangible asset in all other cases. The article analyzes possible accounting treatments for cryptocurrency based on its economic characteristics and challenges the soundness of this interpretative IFRIC agenda decision in terms of the relevance and usefulness of information about cryptocurrencies in entity`s financial statements for their users. However, cryptocurrency does not have the typical features of an intangible asset or an inventory, but rather a financial asset (although it does not meet the current definition of a financial asset in IAS 32 Financial Instruments: Presentation) because an entity can realize a direct cash flow through selling it or using it as a medium of exchange.Therefore, most relevant and useful information is provided when treating it as a financial asset. This conclusion is also supported by the prevailing practice applied by many companies worldwide. For that reason, the International Accounting Standards Board (IASB) should review either the definition of cash (or cash equivalent) in IAS 7 Cash Flow Statements to include cryptocurrencies in its scope, or the definition of a financial asset (other than cash).
Keywords: Cryptocurrency; Bitcoin; Blockchain; Cryptocurrency mining; IFRS; A financial asset model; An intangible asset model; An inventory model